Sosialisasi Kompres Hangat dan Kompres Dingin pada Berbagai Masalah Kesehatan di Desa Miruk Lam Reudep Kecamatan Baitussalam Aceh Besar - Yadi Putra; Fauziah Fauziah; Muhammad Daud; Evi Hafriani; Nivi Sara Ivantaya; Nasrizal Nasrizal (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service aims to increase the knowledge of the community in performing the first treatment of health problems experienced, especially by using warm compresses and cold compresses. The socialisation method uses lectures and questions and answers, power point media, projectors and props. This community service was carried out in collaboration with the Diploma III Nursing Study Program, Faculty of Health Sciences, Abulyatama University in collaboration with Miruk Lam Reudep Village, activities attended by 50 people. The results of the service provide increased knowledge to the community about using compresses in various health cases properly and in accordance with health conditions. The conclusion that this socialisation is very good for dealing with health conditions experienced at that time.